Central Nonenhancement Sign in Carotid Body Tumor on CT Angiography - Mishra, Dewansh; Kesavadas, Chandrasekharan; Thomas, Bejoy; Pujari, Vishnu Shivshankar; Ignatius, Amalan (Indian Journal of Radiology and Imaging, 2023)
Carotid body tumors are rare benign tumors that arise in the carotid space of neck typically presenting as soft to firm, painless swelling in the neck. While specific imaging characteristics have been previously described for carotid body tumors, we report a new imaging sign in three cases of carotid body tumors on computed tomography angiography.
Keywords: carotid body tumor; carotid space paraganglioma; CT angiography; neck masses